Effectiveness of Farmer’s Training in Nepal: A Review - Baral R., Sudikshya; Gyawali , Kiran (JOURNAL OF ADVANCES IN AGRICULTURE, 2024)
Farmer’s training is a method of agricultural extension service delivery. This paper through a thorough review of literature aims to access the effectiveness of farmer training programs in Nepal for transfer of knowledge, creation of awareness, adoption of improved practices and technologies, and improvement in farmer efficiency and farm productivity.